Phylogenomics and evolution of secondary metabolism in plant-associated fungi. (August 2015) - Spatafora, Joseph W; Bushley, Kathryn E
Highlights: Secondary metabolites are small, bioactive molecules that function in fungal ecology. Genomic sequencing has revealed greater diversity of secondary metabolite clusters than previously detected. The modular nature of some secondary metabolite core genes promotes evolutionary and functional diversification. Duplication and divergence and module fusion are two major drivers of NRPS diversification. Abstract : Fungi produce a myriad of secondary metabolites, compounds that are not required for basic cellular processes, but are thought to be central to ecological functions. Genomic sequencing of fungi has revealed a greater diversity of secondary metabolism than previously realized, including novel taxonomic distributions of known compounds and uncharacterized gene clusters in well-studied organisms. Here we provide an overview of the major groups of metabolites, their ecological functions, the genetic systems that produce them, and the patterns and processes associated with evolutionary diversification of secondary metabolism in plant-associated filamentous ascomycetes.